Sport and physical activity in the modern world - Polidoro, J. Richard. (Allyn and Bacon, 2000)
Sport and physical activity in ancient Greece. Sport and physical activity in nationalistic Europe. Sport and physical activity in modern America. The genesis of international sports. International sports in the twentieth century. The development of opportunities and programs for women...